The Safe Learning Environment in the United Arab Emirates Schools and Its Relationship to the Development of Creative Thinking Among Students - Mohammad Salman AlKhaza'leh; Bilal F. Obeidat; Samer Abdel-Hadi; Reema Al Qaruty (Emerging Science Journal, 2023)
The study aimed to assess the relationship between a safe learning environment in Emirati schools and the development of student's creative thinking. Using a descriptive method with stratified random sampling, the researchers selected a sample of 500 male and female teachers. Two questionnaires were employed: one assessing the safe learning environment (20 items) and another measuring creative thinking (20 items). Results indicated a high teacher perception of a safe learning environment, with statistically significant chi-square values for all items. Similarly, teachers perceived a high level of creative thinking development, with significant chi-square values for all items. Gender and experience did not show statistically significant differences in the perception of a safe learning environment. However, teachers with over 10 years of experience demonstrated higher levels of creative thinking development. Notably, a significant correlation was found between a safe learning environment and the development of students' creative thinking in Emirati schools. This study aligns with the UAE Ministry of Education's mission to create a safe and creative educational system that meets the needs of a globally competitive knowledge society. Doi: 10.28991/ESJ-2023-SIED2-014 Full Text: PDF